Personnel Suitability for Employment in Security Agencies - Alispahić, Bakir (Kriminalističke teme, 2018)
Reason(s) for writing and research problem(s): Inspiration for this research paper stems from the fact that there is a lack of ready resources for the security realm because all the knowledge and skills are not equally required for variety of jobs in different ranks and age groups. Aims of the paper (scientific and/or social): The most important goal of the research paper is to shed light on characteristics of the personnel selection in the realm of the security, as well as on the specifics of the education process that has to be adapted to specific activites. Methodology/Design: Methodological work seeks to analyse the possibilities of implementing various scientific achievements in selection and work of security services’ personnel. By synthesising, we aim to propose a functional scientific profile of personnel in relation to the complexity of jobs they are to do. Research/paper limitations: The paper focuses on defining an adequate personnel profile in the field of security and it does not discuss the possibility of generalizing related profile in other field of social action. Results/Findings: On the basis of analysed data and bibliography, a model is proposed that, according to the authors’ opinion, presents the adequate procedure of personnel selection for the jobs within the security realm. Within this model, on the basis of comparison, specific profiles of personnel have been derived in relation to the specifics of certain jobs. General conclusion: On the basis of prognostic research, future personnel needs are conceptualized in accordance with generations and personnel profiles, which directly and continually have to be innovated. Research/paper validity: The function of protection of the society and its values has to be assigned to capable personnel, which is the purpose and justification of this research.